TARKIB IDHAFI DALAM KITAB ADDARDIR ALA QISHATUL MI'RAJ KARYA SYEKH NAJMUDDIN AL-GHAITI - Ufi Fadilah; Akmaliyah Akmaliyah; Irfan Addriadi (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to identify the types and functions of tarkib iḍafi constructions in Kitab ad-Dardir ʿala Qissat al-Miʿraj by Shaykh Najmuddin al-Ghaiṭi, based on the grammatical theory of Imam Ibn Malik. The research is motivated by the complexity of iḍafah structures in classical Arabic texts, which often carry deep grammatical and semantic meanings. This research employs a descriptive-analytical method with a qualitative approach through a library-based study. The data consist of 132 iḍafah phrases collected directly from the text. The analysis was conducted through three stages: identifying iḍafah forms, classifying their types and functions, and interpreting their meanings based on the theories of Ibn Malik and Sharh Ibn ʿAqil. The findings reveal two types of iḍafah: idhafah maʿnawiyyah (semantic genitive) and idhafah lafẓiyyah (phonetic genitive). Of the total data, 116 phrases are categorized as idhafah maʿnawiyyah, and 16 phrases as idhafah lafẓiyyah. In terms of function, 72 iḍafah constructions serve the function of taʿrif (definition), 43 serve takhsis (specification), and 17 serve takhfif (phonetic lightening). These findings indicate that the iḍafah constructions in this text are primarily used to clarify and define meaning semantically (maʿnawiyyah) rather than phonetically (lafẓiyyah). This study contributes to the understanding of Arabic syntactic structures and enriches the study of classical Arabic grammar in academic contexts.